(untitled) (San Francisco, 1998)
The book covers both fundamental research and applied innovations in the key areas of IUI, including input analysis, output generation, user- and discourse-adapted interaction, agent-based interaction, model-based interface design, and evaluation
Keywords: Human-computer interaction,User interfaces ( computer systems )